UPAYA PELESTARIAN LINGKUNGAN MELALUI PENANAMAN BIBIT POHON DI DESA PALAAN, KABUPATEN MALANG - Mojibur Rohman; Mochamad Sulaiman; Alfi Fadliana; Bella Cornelia Tjiptady; Priska Choirina (Jurnal Andalas: Rekayasa dan Penerapan Teknologi, 2021)
Environmental problems are very important issues for humanity to pay attention to. The existence of an environment with healthy, clean and beautiful conditions can provide many benefits for the survival of the community. This time, community service activities focus on environmental issues which are one of the life supports for the surrounding community in Palaan village. The main objective of this activity is to preserve and improve the reforestation process in Palaan village, Ngajum sub-district, Malang district. In addition, through this tree seed planting activity, it is hoped that it can increase the awareness of the village community on the importance of preserving the environment so that it is greener and healthier. In general, community service activities are carried out through three main stages starting from preparation, implementation and evaluation. This service activity involved students from the Faculty of Science and Technology (Saintek) Unira Malang. The process of planting seedlings is carried out in stages for 2 days. The results of the activity showed that 100 tree seedlings had been successfully planted in Palaan Village which had been designated as the planting location. Student participation showed high enthusiasm during the activity which was seen with 45 students being actively involved.